How Does a Sport Psychological Intervention Help Professional Cyclists to Cope With Their Mental Health During the COVID-19 Lockdown? - Bertollo, Maurizio; Forzini, Fabio; Biondi, Sara; Di Liborio, Massimiliano; Vaccaro, Maria Grazia; Georgiadis, Emmanouil; Conti, Cristiana (Frontiers in Psychology, 2021)
All around the word in March, due to COVID-19, competitive sport calendars were suddenly cancelled jeopardizing training programming of athletes. Italian cyclists were banned from leaving their homes and therefore unable to perform their ordinary training activities. The Italian Association of Professional Cyclists (ACCPI) early on during that period, noticed that several cyclists were experiencing a worrying decrease in their mental well-being and asked the authors to set-up an online Sport Psychology Intervention (SPI) during lockdown to enhance the athletes’ mental health. Through a number of unprecedented events and considerations, the aim of the current investigation was to assess the Italian cyclists’ mental health during the lockdown and its changes after the SPI. We validated the Italian version of the Sport Mental Health Continuum Short Form (Sport MHC-SF) –presented in Study 1– and then applied it to a sample of Italian professional cyclists – presented in Study 2 – prior to and after the SPI. To achieve these objectives, the reliability and construct validity of the Italian version of the Sport MHC-SF were tested in Study 1. RM-MANOVA tests run to evaluate the effect of SPI on cyclists in Study 2. A total of 185 athletes were involved in the validation of the MHC in Study 1 and 38 professional cyclists in Study 2. Results from Study 1 suggested a 3-factor higher order model of Sport MHC-SF (Model fit: χ2(df) = 471.252 (252), p<.000; CFI = 0.951; RMSEA = .049; RMR= .048). MCFA showed that the default model kept invariance among groups of athletes (i. e. female, male, individual and team sports). Results from Study 2 highlighted that professional cyclists who followed the SPI were able to cope better with psychological stressors showing improved well-being compared to the athletes that did not. No significant differences were found for emotional and social well-being. The present multi-study paper contributes to the theoretical field with a validated measure of Sport MHC-SF translated in the Italian language and culture. It also provides practical implications related to cases of reduced mental health due to injury, illness or similar situations of home confinement in the future